ANALYSIS OF CASE MANAGER FUNCTIONS IN IMPROVING QUALITY CONTROL AND COST CONTROL OF INPATIENT (CASE STUDY) AT GRANDMED HOSPITAL LUBUK PAKAM - Fitri Maya Sari Panjaitan; Kasim, Felix; Br Ginting Munthe, Novita (JURNAL KESMAS DAN GIZI (JKG), 2023)
Abstract The hospital has a process for implementing continuity of care in the hospital and integration between care-giving professionals (PPA) assisted by a patient service manager (MPP)/case manager. The current challenge that must be faced by hospitals in implementing the JKN program is implementing good quality control and cost control. The existence of MPP in the hospital case management system is expected to be able to support quality control and cost control. The purpose of this study was to analyze the functions of the case manager in improving quality control and cost control for inpatients (case study). This research was conducted at the Grandmed Lubuk Pakam Hospital, Deli Serdang Regency from September 2022 to May 2023. The type of research in this study was qualitative. The sample in this study were case managers at Grandmed Lubuk Pakam Hospital, Deli Serdang Regency, totaling 3 people and 1 director of medical services and 3 heads of inpatient rooms. The results showed that the implementation of case managers in improving quality control and cost control for inpatients was quite good. The case manager utility assessment has not gone well because there is no clear format for the initial screening of patients. Patient care planning by case managers has not been maximized. Not all case managers do patient care planning. The case manager's facilitation and advocacy has not been maximized. There are 2 case managers who do not coordinate with other fields, only coordinate with DPJP and nurses. The case manager evaluation has not gone well because there is no instrument format for case manager tasks so evaluation cannot be carried out. Post-discharge planning follow-up by the case manager has not gone well because the case manager has never followed up post-discharge planning. Case managers should carry out case manager functions for patients who are being treated in case management in accordance with the standard criteria set by STARKES 2022 accompanied by proper and accurate documentation to improve service quality and patient satisfaction. Keywords : Functions, Case Manager, Quality Control, Cost Control, Hospitalization, Case Study